Frequency of Iodine Deficiency Disorders Among Children Living in the Iodine Deficiency Region - Tamila Sorokman; Marina Bachu; Iryna Sokolhyk (Amaltea Medical Publishing House, 2021)
Introduction. Currently, only a small number of countries have a stable iodine adequacy, about a third of the world's population lives in areas with some iodine deficiency. Because children have an increased risk of adverse effects in response to iodine deficiency, it is important to assess the health of these children.Aim. To investigate the frequency of iodine deficiency in children from the iodine deficiency region.Methods. The research was conducted during expeditions to various geographical areas of Northern Bukovyna (Chernivtsi region, Ukraine). 1,973 school-age children were examined (measurement of anthropometric indicators, assessment of cognitive, physical and sexual development, ultrasonography of the thyroid gland (TG), ovaries and testicles, determination of hormonal status and iodine in urine).Results. Of 1,973 children, 53.7% (1060) had thyroid abnormalities. The frequency of goiter in the mountain zone - 59.8%. In 12.3% of children there was a tendency to increase of TSH. The median ioduria in children from moun-tainous areas corresponds to moderate iodine deficiency. Children from mountainous areas have various disorders: 38.5% disharmonious physical development, a third low intellectual development, disorders of the order of appear-ance and development of secondary sexual characteristics in the examined children.Conclusion. The results of the study show the negative impact of iodine deficiency on the body of children. It is necessary to continue monitoring of ioduria and children's health and implement preventive measures.